Una estrategia en metamorfosis: logros, trabas y perspectivas de la reforma en China - Yang, Enrique Enrui (Huarte de San Juan. Geografía e Historia, 2006)
Thanks to the great efforts of economic openess towards modernization –this strategy has been adopted by China during three last decades–, achievements relating growing of its gross national product have been amazing, and, in consequence, growing of its international presence. However, economical improvements confront great socioeoonomical and ecological difficulties, what arise the question of its uncertain future, unless their origin in the institutional system is eradicated through a deep reform. There is great expectations to see if China will continue to play, together with the United States, its leading role in the international arena. This will be conditioned by a political redefinition of its national issues. This paper aims to analize the progress of Chinese reform, pointing out its uncommon line until today, as well as introducing its present burning problems, and all this faced with the reaction of the Comunist Party.